Effects of a whole-body electrostimulation program on strength, sprinting, jumping, and kicking capacity in elite soccer players - Filipovic, A.; Grau, M.; Kleinöder, H.; Zimmer, P.; Hollmann, W.; Bloch, W. (Journal of Sports Science & Medicine, 2016)
The aim of the present study was to investigate the effect of a 14-week dynamic Whole-Body Electrostimulation (WB-EMS) training program on muscular strength, soccer relevant sprint, jump and kicking velocity performance in elite soccer players during competitive season. Twenty-two field-players were assigned to 2 groups: WB-EMS group (EG, n = 12), jump-training group (TG, n = 10). The training programs were conducted twice a week concurrent to 6-7 soccer training sessions during the 2nd half of the season. Participants were tested before (baseline), during (wk-7) and after (wk-14). Blood serum samples for analyzing IGF-1 and CK were taken before each testing, 15-30min post and 24h post the training program. Our findings of the present study were that a 14-week in-season WB-EMS program significant increased one-leg maximal strength (1RM) at the leg press machine (1.99 vs. 1.66 kg/kg, p = 0.001), and improved linear sprinting (5m: 1.01 vs. 1.04s, p=0.039), sprinting with direction changes (3.07 vs. 3.25s, p = 0.024), and vertical jumping performance (SJ: 38.8 vs. 35.9cm p = 0.021) as well as kicking velocity (1step: 93.8 vs. 83.9 km·h-1, p < 0.001). The TG showed no changes in strength and performance. The EG revealed significantly increased CK levels 24h post training and yielded significantly higher CK levels compared to the TG. IGF-1 serum levels neither changed in the EG nor in the TG. The results give first hints that two sessions of a dynamic WB-EMS training in addition to 6-7 soccer sessions per week can be effective for significantly enhancing soccer relevant performance capacities in professional players during competitive season.